Multiplikasi Tunas In Vitro Anggrek Phalaenopsis dan Analisis Keragaman Genetik dengan Marka SNAP: Shoot Multiplication of Phalaenopsis Orchid in BAP Treatment Medium and The Genetic Diversity Analysis of Clonal Plantlets with SNAP Marker - Mira Humaira; Agus Purwito; Sudarsono; Sukma, Dewi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2020)
Clonal propagation of orchid by in vitro culture is needed to obtain the high quantity and quality of orchid propagules. This study aimed to understand the effect of BAP (benzyl amino purine) concentrations on the shoot multiplication of three Phalaenopsis hybrid populations and to analyze genetic diversity using Pto-SNAP markers on clonal plantlets. The experiments were performed separately for each population, namely shoots from seed germination of Phal. amabilis x Phal. ‘KHM 421’ with five level of BAP (0.00, 11.09, 22.19, 33.29, 44.39 µM), clonal shoots from Phal. ‘Salu Spot’ x Phal. bellina ‘1102-38’, and Phal. ‘Salu Spot’ x Phal. bellina ‘1102-44’ with four level of BAP (11.09, 22.19, 33.29, 44.39 µM). The results showed that the optimum BAP concentration for shoot multiplication on three population was 22.19 µM which shoot number obtained were 3.7, 4.7, and 6.0 at 12 week after planting (WAP). Protocorm like bodies (PLBs) was only produced on Phal. amabilis x Phal. ‘KHM 421’ population, which the highest number of PLBs was on 11.09 BAP. Evaluation of genetic diversity using 11 Pto-SNAP (single nucleotide amplified polymorphism) marker was performed on Phal. ‘Salu Spot’ x Phal. bellina ‘1102-44’ shoots. The results revealed the presence of somaclonal variation with 7.7% of genetic diversity of the shoots from BAP 22.19 µM treatment at Pto-241 and 11.1% from BAP 44.39 µM treatment at Pto-424.Keywords: clonal propagation, cytokinin, molecular markers, orchid, Pto, somaclonal variation